CONSUMERS BUYING BEHAVIOUR ON SHOPPING AT MALLS- COMPARATIVE STUDY FROM THE PERSPECTIVES OF URBAN AND RURAL COSUMERS. - Arya Soman (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
A comprehensive understanding of consumer behaviour is essential to the long- run success of any marketing program. It is seen as a one of the major component of the marketing concept. The availability of the products services at the shopping malls acts as an information to the buyer. Shopping malls acts as a key source of information to the consumers. Consumers are frequently researched due to the fact that the choices related to their purchases are considerably influenced by their behavioral patterns or unique activities at the market place. Shopping malls acts as a bridge between the consumers and the retailers to categorize the various assortments and also to target the profitable consumers. The perception of the consumers will form a substantial influence factor in determining the choices of wide ranging products/services offered by the shopping malls.